Characteristic of acan: a traditional shrimp paste of Maduranese, Indonesia. (February 2019) - Ali, Mahrus; Yunianta,; Aulanni'am,; Kusnadi, Joni
Abstract: Acan is a typical fermented product from Maduranese, Indonesia. The product made from small shrimp called odhang acan or geraguh ( Acetes sp.). Acan is a traditional condiment and has a distinctive aroma and flavor. This study aim is to identify the characteristics of Maduranese acan including raw material, fishing gears, manufacturing process, physical properties, chemical, and microbial profiles of the product. This research conducted by survey and interview technique, following by laboratory checking of the quality profile of the product. The results of the study indicate that acan produced by SMEs in Madura. The production of acan is quite simple through fermentation technology which added with 5-10% solar salt. Product properties have different characteristics depended on processing steps and fermentation period. Generally, the quality of acan has a convenient to the Indonesian shrimp paste standard product (SNI).